2016
DOI: 10.1002/chem.201605622
|View full text |Cite
|
Sign up to set email alerts
|

Frustrated Lewis Pair‐Like Reactivity of Rare‐Earth Metal Complexes: 1,4‐Addition Reactions and Polymerizations of Conjugated Polar Alkenes

Abstract: Three rare-earth aryloxide ion pairs {[L1REOAr] /[B(C F ) ] ; L1=CH C(2,6-iPr C H N)CHC(CH )(NCH CH PPh ); RE=Sc, Y, Lu; Ar=2,6-tBu C H } were reported that feature rare-earth/phosphorus (RE/P) combinations exhibiting frustrated Lewis pair (FLP)-like 1,4-addition reactions towards conjugated carbonyl substrates (e.g., enone, ynone, and acrylic substrates). Furthermore, these RE/P complexes were found to be effective catalysts for the polymerization of conjugated polar alkene monomers. Mechanistic studies revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 61 publications
3
27
0
Order By: Relevance
“…Nevertheless, a quantitative monomer consumption was realized in 20 min by adding an additional equivalent of the Sc complex 1 ( Table 2 , entry 4). These observations indicated that the polymerization requires another equivalent of Lewis acid to activate monomer, which is consistent with the activated monomer propagation mechanism [ 23 , 24 , 25 , 26 , 29 , 30 ].…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Nevertheless, a quantitative monomer consumption was realized in 20 min by adding an additional equivalent of the Sc complex 1 ( Table 2 , entry 4). These observations indicated that the polymerization requires another equivalent of Lewis acid to activate monomer, which is consistent with the activated monomer propagation mechanism [ 23 , 24 , 25 , 26 , 29 , 30 ].…”
Section: Resultssupporting
confidence: 69%
“…Inspired by flourishing frustrated Lewis pairs (FLPs) chemistry [ 21 , 22 ], Lewis pair polymerization (LPP) of polar alkenes by main-group Al- or B-based Lewis pairs was successfully achieved in recent years [ 23 , 24 , 25 , 26 , 27 , 28 ]. We reported the polymerization of methyl methacrylate (MMA) and its cyclic analogues by using the intramolecular cationic rare-earth (RE)-based Lewis pairs [ 29 ]. Subsequently, enhanced polymerization activity and extended monomer scope were realized by utilizing simple intermolecular Lewis pairs which are composed of homoleptic rare-earth metal tris-aryloxides RE(OAr) 3 and phosphines PR 3 [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Xu and co-workers [71,72] developed unique, rareearth metal-based LPs. They consist of rare-earth metal such as Sc, Y, or Lu and the ancillary ligand of phosphorus-tethered Scheme 6.…”
Section: Rare-earth Metal-or Si-based Lpsmentioning
confidence: 99%
“…Lewis pair (LP) polymerization has emerged and attracted intense investigations of the cooperative (or synergistic) catalytic effects of Lewis acid (LA) and Lewis base (LB) pairs on the polymerization of conjugated polar alkenes [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ], since the seminal works on Frustrated Lewis Pairs (FLPs) by Stephan and Erker in small molecule chemistry [ 9 , 10 , 11 , 12 ]. For instance, LPs based on strongly acidic, bulky E(C 6 F 5 ) 3 (E = B, Al) LAs and bulky LBs including phosphines and N -heterocyclic carbenes (NHCs) have been employed to initiate rapid addition polymerization of conjugated polar vinyl monomers such as methyl methacrylate (MMA), cyclic and the naturally renewable monomers α-methylene-γ-butyrolactone (MBL), and γ-methyl-α-methylene-γ-butyrolactone (MMBL) [ 13 , 14 , 15 ] and monomers bearing the C=C–C=N functionality such as 2-vinylpyridine and 2-isopropenyl-2-oxazoline as well [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%